Damage behavior and maintenance design of tunnel lining based on numerical evaluation. (January 2020) - Liu, Shouhua; Shi, Yao; Sun, Rui; Yang, Junsheng
Highlights: Cracking and spalling behaviors of the lining of the tunnel are examined. The lining failure is caused by insufficient lining thickness. The mechanical response of a tunnel structure is analyzed using XFEM. The inner lining is an effective maintenance method in similar tunnels. Abstract: The cracking and spalling of lining will adverse impact on the serviceability and durability of the tunnel. Thus, corresponding maintenance work to repair this damage in the tunnel structure is pertinent to its longevity. In this study, the cracking and spalling behaviors of the lining within an operational tunnel structure are examined. An integrated field investigation is conducted to characterize the spatial distribution of the damage, and the lining failure is speculated to be caused by insufficient lining thickness. To further understanding of the influence of insufficient lining thickness on the lining structure performance, extended finite element method (XFEM), is used to conduct a reliable numerical simulation. According to the maximum tension strain, failure evolution, safety factors of the failure region obtained by XFEM, the simulation results generally agree with the actual lining damage forms. This work demonstrates that serious lining damage is directly caused by insufficient lining thickness. Ultimately, a specific maintenance method is developed and simulated based on the deficiencies in tunnel construction. The proposed maintenance method is confirmed to be efficient and safe according numerical results.